2002
DOI: 10.1016/s0378-1097(02)00935-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Leptospira interrogans locus containing DNA replication genes and a new IS, IS1502

Abstract: A region of the Leptospira interrogans serovar pomona genome encoding DNA replication genes was characterized. This region, designated the ppa-ntrC locus, includes 19 open reading frames and a new insertion sequence, IS1502. Although this locus resembles replication origins from many eubacteria, it lacks several genes common to homologous loci. Some replication-related genes were previously located near rrf, and may have been moved to that location by homologous recombination between short sequence elements co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…L. interrogans genome data varied widely from pathogenic spirochetes, Treponema pallidum and Borrelia burgdorferi, although they show considerable similarities in the genes that are responsible for their unique morphological features. Comparative genomics revealed both overall genetic similarities and significant structural differences, including a large chromosomal inversion and extensive variation in the number and distribution of insertion sequence elements, thus confirming genome plasticity as suggested by several previous studies [161,170,171,180,181]. The genomes of L. borgpetersenii showed approximately 700 kb reduction compared to L. interrogans and revealed substantial differences in genetic content and organization.…”
Section: Whole Genome Sequencingsupporting
confidence: 84%
“…L. interrogans genome data varied widely from pathogenic spirochetes, Treponema pallidum and Borrelia burgdorferi, although they show considerable similarities in the genes that are responsible for their unique morphological features. Comparative genomics revealed both overall genetic similarities and significant structural differences, including a large chromosomal inversion and extensive variation in the number and distribution of insertion sequence elements, thus confirming genome plasticity as suggested by several previous studies [161,170,171,180,181]. The genomes of L. borgpetersenii showed approximately 700 kb reduction compared to L. interrogans and revealed substantial differences in genetic content and organization.…”
Section: Whole Genome Sequencingsupporting
confidence: 84%
“…IS1500 (3) is equally distributed in both genomes (eight copies), the only difference being that in serovar Lai one copy invaded the CII replicon, which has not previously been described. Reminiscent insertions of IS1533 (51) and IS1502 (52) are found at the same relative locations in both genomes.…”
Section: Resultsmentioning
confidence: 90%
“…Our analysis of the L. interrogans genome revealed the presence of the previously described insertion sequence (IS) elements IS1500, IS1501 (58), reminiscent insertions of IS1533 (59) and IS1502 (60) and an IS recently identified that we designated ISlin1 (5) ( Table 2). IS1500, IS1501 and ISlin1 account for 24 insertions distributed throughout chromosome I.…”
Section: Comparative Genomics and Insertion Sequencesmentioning
confidence: 88%